Lighting the barricades: affective artefacts for the transmission of memory of the anti-dictatorial movement in Chile (1983-1986) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article we analyze the use of the barricade as a key affective artefact in the generational transmission of the memory of the anti-dictatorial resistance movement in Chile (1983-1986). To do this, we explore the relationship between affects, meanings and rituals involved in activating this device focusing our analysis on historically marginalized areas of Santiago. Usually described by the press as vandalism, barricades have been studied by the field of social movements studies as repertoires of protests, yet in the field of memory studies they have not taken a central place as commemorative elements. Based on a qualitative study that inclu- ded the analysis of in-depth interviews, participant observation and analysis of documentary sources, we propose to understand the barricade as an affective artefact. The analysis suggests that through two main dimensions, a territorialized materiality and a transgressive temporality, this artefact is capable of activating the transmission of memories that have not been included in the official narrative.
Keywords: Barricade, affective artefact, transmission, anti-dictatorial movement